The Effect Of Company Size, Liquidity And Profitability On The Capital Structure Of Automotive Companies Listed In Indonesia Stock Exchange (Idx) For The Period 2014 – 2018. - Zatira, Dhea; Simbolon, Sabam; Sutrisna, Sutrisna (Universitas Buddhi Dharma/Fakultas Bisnis/Program Studi Akuntansi, 2020)
This research aims to determine what factors can influence the capital structure of automotive sub-sector companies listed on the Indonesian stock exchange for the period 2015 - 2018. These factors include company size, liquidity and profitability. The methodology used in this research is quantitative associative with secondary data sources that come from financial reports that have been published by companies and the IDX. The data analysis technique in this study used a panel data regression model with E-Views software. The results of this study indicate that firm size has no effect on capital structure, which can be seen from this value t statistic 0.492999 0.05. Liquidity has an effect on the Capital Structure which can be seen from the t-table value of -7.788281> t-table 2.039 and the probability value of 0.0000 0.05. Simultaneously the variable company size, liquidity and profitability have an effect on the capital structure which can be seen from the value obtained by the F-table value of 2.91, which means that the F-count is 22.32849> Ftable 2.91 and the probability value of F-statistic is 0.00000 ​